Flight anxiety: investigating the role of airline service quality and flight crew's competence. Issue 7 (3rd July 2019) - Batouei, Amir; Iranmanesh, Mohammad; Nikbin, Davoud; Hyun, Sunghyup Sean
ABSTRACT: The aims of this study were to investigate the role of airlines' service quality and flight crew's competence on travellers' flight anxiety and satisfaction and to examine whether flight anxiety and satisfaction are related to travellers' loyalty. Partial least squares analysis, with empirical data from 262 travellers, was employed to assess the proposed conceptual model. Results indicated that flight crew's competence and service quality are significantly related to both flight anxiety and travellers' satisfaction. Travellers' satisfaction was found to affect travellers' loyalty, while the effect of flight anxiety on travellers' loyalty was not supported.